Comparison of Younger and Older medical student performance outcomes: A retrospective analysis in Japan. - Nobuyasu Komasawa; Fumio Terasaki; Kimitaka Takitani; Sang-Woong Lee; Ryo Kawata; Takashi Nakano; Komasawa, Nobuyasu; Terasaki, Fumio; Takitani, Kimitaka; Lee, Sang-Woong; Kawata, Ryo; Nakano, Takashi (Medicine, 2022)
The present study examined the impact of age on medical student repeat-year experience and performance outcomes on the objective structured clinical examination (OSCE), Clinical Clerkship (CC), and other relevant examinations in the Japanese medical school system. This retrospective analysis examined the number of students with repeat-years and the years required to graduate, stratifying students by the age they entered medical school (Younger: within 4 years of high school graduation; Older: 5 or more years after high school graduation). Scores of the Pre-CC OSCE, Computer-based testing (CBT), CC performance, CC integrative test, and graduation exams were compared among those graduating from our medical school between 2018 and 2020, and examined correlations between student age and performance outcomes. From 2018 to 2020, 328 medical students graduated. Of these, 283 had entered within 4 years of high school graduation (Younger), while 45 did so 5 or more years after high school graduation (Older). The number of repeat-years did not differ significantly between groups. The average number of years required to graduate was slightly higher for the Older group and the Younger group scored significantly higher on the CC integrative test. No significant differences were found for the remaining tests. These results suggest that older medical students in general show no significant inferiority in their performance of most clinical skills and competencies relative to younger students in Japan.